Interplay between lung and intestine in responses to diesel exhaust particles: Contrasting intestinal effects of cleared and swallowed particles with lung-mediated effects using an in vitro approach - Gowsinth Gunasingam; Ruiwen He; Roman M. Fortunatus; Jorge Larios; Mauro Sousa de Almeida; Sandor Balog; Johan Øvrevik; Alke Petri-Fink; Barbara Rothen-Rutishauser (Environmental Pollution, 2026)

Immunostimulatory nanoparticles delivering cytokines as a novel cancer nanoadjuvant to empower glioblastoma immunotherapy - Flávia Sousa; Henry Lee; Mauro Almeida; Amelie Bazzoni; Barbara Rothen-Rutishauser; Alke Petri-Fink (Drug Delivery and Translational Research, 2024)
Glioblastoma (GBM) stands as a highly aggressive and deadly malignant primary brain tumor with a median survival time of under 15 months upon disease diagnosis. While immunotherapies have shown promising results in solid cancers, brain cancers are still unresponsive to immunotherapy due to immunological dysfunction and the presence of a blood–brain barrier. Interleukin-12 (IL-12) emerges as a potent cytokine in fostering anti-tumor immunity by triggering interferon-gamma production in T and natural killer cells and changing macrophages to a tumoricidal phenotype. However, systemic administration of IL-12 toxicity in clinical trials often leads to significant toxicity, posing a critical hurdle. To overcome this major drawback, we have formulated a novel nanoadjuvant composed of immunostimulatory nanoparticles (ISN) loaded with IL-12 to decrease IL-12 toxicity and enhance the immune response by macrophages and GBM cancer cells. Our in vitro results reveal that ISN substantially increase the production of pro-inflammatory cytokines in GBM cancer cells (e.g. 2.6 × increase in IL-8 expression compared to free IL-12) and macrophages (e.g. 2 × increase in TNF-α expression and 6 × increase in IL-6 expression compared to the free IL-12). These findings suggest a potential modulation of the tumor microenvironment. Additionally, our study demonstrates the effective intracellular delivery of IL-12 by ISN, triggering alterations in the levels of pro-inflammatory cytokines at both transcriptional and protein expression levels. These results highlight the promise of the nanoadjuvant as a prospective platform for resharing the GBM microenvironment and empowering immunotherapy. Graphical Abstract

Detection of submicron- and nanoplastics spiked in environmental fresh- and saltwater with Raman spectroscopy - Jessica Caldwell; Laura Rodriguez-Lorenzo; Begoña Espiña; Aaron Beck; Friederike Stock; Kathrin Voges; Katsia Pabortsava; Christopher Feltham; Alice Horton; Richard Lampitt; Barbara Rothen-Rutishauser; Patricia Taladriz-Blanco; et al. (Marine Pollution Bulletin, 2024)

Transferability and reproducibility of exposed air-liquid interface co-culture lung models - Hedwig M. Braakhuis; Eric R. Gremmer; Anne Bannuscher; Barbara Drasler; Sandeep Keshavan; Barbara Rothen-Rutishauser; Barbara Birk; Andreas Verlohner; Robert Landsiedel; Kirsty Meldrum; Shareen H. Doak; Martin J.D. Clift; et al. (NanoImpact, 2023)

Gene expression profiling of human macrophages after graphene oxide and graphene nanoplatelets treatment reveals particle-specific regulation of pathways - Daria Korejwo; Savvina Chortarea; Chrysovalanto Louka; Marija Buljan; Barbara Rothen-Rutishauser; Peter Wick; Tina Buerki-Thurnherr (NanoImpact, 2023)

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

A novel 3D intestine barrier model to study the immune response upon exposure to microplastics - Roman Lehner; Wendel Wohlleben; Dedy Septiadi; Robert Landsiedel; Alke Petri-Fink; Barbara Rothen-Rutishauser (Archives of Toxicology, 2020)

Biological response of an in vitro human 3D lung cell model exposed to brake wear debris varies based on brake pad formulation - Hana Barosova; Savvina Chortarea; Pavlina Peikertova; Martin J. D. Clift; Alke Petri-Fink; Jana Kukutschova; Barbara Rothen-Rutishauser (Archives of Toxicology, 2018)

Erratum to: Biological Effects in Lung Cells In Vitro of Exhaust Aerosols from a Gasoline Passenger Car With and Without Particle Filter - Christoph Bisig; Sandro Steiner; Pierre Comte; Jan Czerwinski; Andreas Mayer; Alke Petri-Fink; Barbara Rothen-Rutishauser (Emission Control Science and Technology, 2017)

Predicting pulmonary fibrosis in humans after exposure to multi-walled carbon nanotubes (MWCNTs) - Monita Sharma; Jake Nikota; Sabina Halappanavar; Vincent Castranova; Barbara Rothen-Rutishauser; Amy J. Clippinger (Archives of Toxicology, 2016)

Diesel exhaust: current knowledge of adverse effects and underlying cellular mechanisms - Sandro Steiner; Christoph Bisig; Alke Petri-Fink; Barbara Rothen-Rutishauser (Archives of Toxicology, 2016)

Expert consensus on an in vitro approach to assess pulmonary fibrogenic potential of aerosolized nanomaterials - Amy J. Clippinger; Arti Ahluwalia; David Allen; James C. Bonner; Warren Casey; Vincent Castranova; Raymond M. David; Sabina Halappanavar; Jon A. Hotchkiss; Annie M. Jarabek; Monika Maier; William Polk; et al. (Archives of Toxicology, 2016)

Biological Effects in Lung Cells In Vitro of Exhaust Aerosols from a Gasoline Passenger Car With and Without Particle Filter - Christoph Bisig; Sandro Steiner; Pierre Comte; Jan Czerwinski; Andreas Mayer; Alke Petri-Fink; Barbara Rothen-Rutishauser (Emission Control Science and Technology, 2015)

Macroscopic to microscopic scales of particle dosimetry: from source to fate in the body - Paul A. Solomon; Peter Gehr; Deborah H. Bennett; Robert F. Phalen; Loyda B. Méndez; Barbara Rothen-Rutishauser; Martin Clift; Christina Brandenberger; Christian Mühlfeld (Air Quality, Atmosphere & Health, 2012)

Nanotoxicology: a perspective and discussion of whether or not in vitro testing is a valid alternative - Martin J. D. Clift; Peter Gehr; Barbara Rothen-Rutishauser (Archives of Toxicology, 2011)

Transfer of Lipophilic Markers from PLGA and Polystyrene Nanoparticles to Caco-2 Monolayers Mimics Particle Uptake - Peter Pietzonka; Barbara Rothen-Rutishauser; Peter Langguth; Heidi Wunderli-Allenspach; Elke Walter; Hans P. Merkle (Pharmaceutical Research, 2002)

A ZO1-GFP fusion protein to study the dynamics of tight junctions in living cells - Franziska K. Riesen; Barbara Rothen-Rutishauser; Heidi Wunderli-Allenspach (Histochemistry and Cell Biology, 2002)

Differences in the Intracellular Distribution of Acid-Sensitive Doxorubicin-Protein Conjugates in Comparison to Free and Liposomal Formulated Doxorubicin as Shown by Confocal Microscopy - Ulrich Beyer; Barbara Rothen-Rutishauser; Clemens Unger; Heidi Wunderli-Allenspach; Felix Kratz (Pharmaceutical Research, 2001)

PHENOTYPIC CHARACTERIZATION OF HUMAN UMBILICAL VEIN ENDOTHELIAL (ECV304) AND URINARY CARCINOMA (T24) CELLS: ENDOTHELIAL VERSUS EPITHELIAL FEATURES - KAYOSHI SUDA; BARBARA ROTHEN-RUTISHAUSER; MAJA GÜNTHERT; HEIDI WUNDERLI-ALLENSPACH (In Vitro Cellular & Developmental Biology - Animal, 2001)

Formation of Multilayers in the Caco-2 Cell Culture Model: A Confocal Laser Scanning Microscopy Study - Barbara Rothen-Rutishauser; Annette Braun; Maja Günthert; Heidi Wunderli-Allenspach (Pharmaceutical Research, 2000)

MDCK Cell Cultures as an Epithelial In Vitro Model: Cytoskeleton and Tight Junctions as Indicators for the Definition of Age-Related Stages by Confocal Microscopy - Barbara Rothen-Rutishauser; Stefanie D. Krämer; Annette Braun; Maja Günthert; Heidi Wunderli-Allenspach (Pharmaceutical Research, 1998)